(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Studies of interaction of flavonoids: morin, quercetin and rutin, with DNA at 0.002 M ionic strength solution have been carried out by square wave voltammetry (SWV) method. SWV curves of the mentioned flavonoids and their complexes with DNA were obtained. Based on titration curves coordinates of r and Cf (Scatchard’s coordinates) were obtained and the curves of r/Cf dependence on r were constructed. Nonlinear binding curves were obtained, which were interpreted from the point of view of existing at least two modes of binding the mentioned flavonoids with DNA. From the curves for two modes of interaction, values of the binding constant (K) and the number of DNA base pairs (n) per one binding molecule of flavonoid were determined.